A cryptographic service provider (CSP) for an FPGA-based cryptohardware system - Khalil-Hani, Mohamed (2007)
A Cryptographic Service Provider (CSP) is a software library that implements the Microsoft CryptoAPI (CAPI). CSPs implement encoding and decoding functions, which computer application programs may use, for example, to implement strong user authentication or for secure email.